Advances in Genetic Reprogramming: Prospects from Developmental Biology to Regenerative Medicine - Dhanjal, Daljeet Singh; Singh, Reena; Sharma, Varun; Nepovimova, Eugenie; Adam, Vojtech; Kuca, Kamil; Chopra, Chirag (Current medicinal chemistry, 2024)
The foundations of cell reprogramming were laid by Yamanaka and co-workers, who showed that somatic cells can be reprogrammed into pluripotent cells (induced pluripotency). Since this discovery, the field of regenerative medicine has seen advancements. For example, because they can differentiate into multiple cell types, pluripotent stem cells are considered vital components in regenerative medicine aimed at the functional restoration of damaged tissue. Despite years of research, both replacement and restoration of failed organs/ tissues have remained elusive scientific feats. However, with the inception of cell engineering and nuclear reprogramming, useful solutions have been identified to counter the need for compatible and sustainable organs. By combining the science underlying genetic engineering and nuclear reprogramming with regenerative medicine, scientists have engineered cells to make gene and stem cell therapies applicable and effective. These approaches have enabled the targeting of various pathways to reprogramme cells, i.e., make them behave in beneficial ways in a patient-specific manner. Technological advancements have clearly supported the concept and realization of regenerative medicine. Genetic engineering is used for tissue engineering and nuclear reprogramming and has led to advances in regenerative medicine. Targeted therapies and replacement of traumatized , damaged, or aged organs can be realized through genetic engineering. Furthermore, the success of these therapies has been validated through thousands of clinical trials. Scientists are currently evaluating induced tissue-specific stem cells (iTSCs), which may lead to tumour-free applications of pluripotency induction. In this review, we present state-of-the-art genetic engineering that has been used in regenerative medicine. We also focus on ways that genetic engineering and nuclear reprogramming have transformed regenerative medicine and have become unique therapeutic niches.
Keywords: Developmental Biology; regenerativní lékařství; Tissue Engineering; vývojová biologie; Genetic Engineering; indukované pluripotentní kmenové buňky; Cellular Reprogramming; Animals; Humans; Induced Pluripotent Stem Cells; genetické inženýrství; lidé; tkáňové inženýrství; Regenerative Medicine; zvířata; přeprogramování buněk